2008
DOI: 10.1111/j.1537-2995.2007.01632.x-i2
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of heparin‐binding protein in transfusion‐related acute lung injury

Abstract: BACKGROUND:In antibody-mediated nonhemolytic transfusion reactions, transfusion-related acute lung injury (TRALI) tends to occur typically within 2 hours after a blood transfusion. White cell antibodies or immune complexes have been frequently shown to be associated with the syndrome, although the mechanisms by which they induce TRALI are poorly understood. The aim of this study was to characterize soluble mediators that are released from cells at an early stage after immune stimulation. STUDY DESIGN AND METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, the mechanism of leukocyte activation after their accumulation in the lung should be carefully investigated thereafter. A recent finding by Yasui et al has revealed the possible involvement of heparin-binding protein as one of the primary effector molecules of antibody-mediated TRALI [59].…”
Section: Pathogenesis Of Tralimentioning
confidence: 99%
“…However, the mechanism of leukocyte activation after their accumulation in the lung should be carefully investigated thereafter. A recent finding by Yasui et al has revealed the possible involvement of heparin-binding protein as one of the primary effector molecules of antibody-mediated TRALI [59].…”
Section: Pathogenesis Of Tralimentioning
confidence: 99%
“…Leukocyte antibodies (e.g. anti-HNA-3a or anti-HLA-A2) stiffen neutrophils or even agglutinate them so that they cannot pass through the narrow lung capillaries and are trapped in the lung where the neutrophils become pro-adhesive (increased CD11b expression) (42), secrete proinflammatory mediators azurocidin, and heparin-binding protein) which can injure the endothelium (40,42,43). In a mouse TRALI model using a monoclonal HLA class I antibody, the occurrence of TRALI was dependent on neutrophils and their Fcγ receptors as well as on platelets and on housing of the mice in a nonpathogen-free barrier room (39,44).…”
Section: Pathophysiology Of Immune Tralimentioning
confidence: 99%